Filled Julia set of some class of Hénon-like maps. Issue 1 (2nd January 2020) - Antonio Caprio, Danilo
ABSTRACT: In this work we consider a class of endomorphisms of R 2 defined by f ( x, y ) = ( x y + c, x ), where c ∈ R is a real number and we prove that when − 1 < c < 0, the forward filled Julia set of f is the union of stable manifolds of fixed and 3 − periodic points of f . We also prove that the backward filled Julia set of f is the union of unstable manifolds of the saddle fixed and 3 − periodic points of f .